Role of Genetic Polymorphisms of Cytochrome P450 2C19 in Pantoprazole Metabolism and Pantoprazole-based Helicobacter pylori Eradication Regimens - Jonaitis, Paulius; Jonaitis, Laimas; Kupcinskas, Juozas (Current Drug Metabolism, 2020)
Background: Cytochrome P450 (CYP450) enzymes play an important role in the metabolism of 70-80% of the currently used medications, including proton pump inhibitors. There are some data analyzing the impact of gene polymorphisms of CYP450 enzymes on most widely used PPIs, such as omeprazole, however, the data on pantoprazole are highly lacking. Objective: To summarize the most recent publications and studies on the role of polymorphisms of the genes encoding CYP450 enzyme 2C19 in the metabolism of pantoprazole and pantoprazole based Helicobacter pylori eradication regimens. Methods: We performed a non-systematic search of the available literature on the selected topic. Results and Conclusion: The data on cytochrome P450 gene polymorphisms and their role in pantoprazole metabolism and pantoprazole based Helicobacter pylori eradication remain conflicting. Individual differences in pantoprazole metabolism might be partly related to genetic polymorphisms of CYP450 enzymes. Most of the studies support the observation that cytochrome 2C19 polymorphisms have an impact on the pharmacokinetics of pantoprazole and its therapeutic effects: poor metabolizers of PPIs are more likely to have a better response to pantoprazole therapy and achieve better H. pylori eradication rates compared to rapid metabolizers. The determination of alleles that are associated with decreased (e.g., *2, *3 alleles) or increased (e.g., *17 allele) cytochrome 2C19 enzyme activity might be used as predictive factors for the potential of acid suppression and the success of Helicobacter pylori eradication. Overall, currently available data do not provide robust evidence, therefore, the application of genetic polymorphisms of cytochrome enzymes in clinical practice still cannot be recommended as routine practice for personalized pantoprazole prescription strategies.
Keywords: cytochrome P450